Mental Health and Its Socioeconomic Inequality in Sweden: The Role of Demographic Changes over Time - Anna Linder; Devon Spika; Ulf-G. Gerdtham; Sara Fritzell; Gawain Heckley (Lund University, School of Economics and Management, Department of Economics, 2018)
Our aim is to study trends in mental ill-health and socioeconomic-related mental health inequalities over time in Sweden. We also make a first attempt at disentangling why we see such a development, by decomposing any changes in terms of changes in selected demographic and socioeconomic characteristics among the population. A secondary aim is to consider how different indicators for mental ill-health, as well as different measures of inequality, affect the conclusions we draw. Register data from the Swedish Interdisciplinary Panel and the Swedish Living Conditions Survey (administered by Statistics Sweden) are used to study trends in mental ill-health and mental health inequalities over the years 1994-2011. The study population comprises of working age individuals aged 31-64 living in Sweden. Four indicators of mental ill-health are used in the main analysis: self-reported anxiety, psychiatric inpatient diagnosis, psychiatric outpatient diagnosis and death by suicide. The results show that psychiatric diagnoses (in- and outpatient) increased substantially amongst 31 - 64 year olds between 1994 and 2011. Self-reported anxiety remained stable and suicides decreased. These results show that the different indicators of mental ill-health are not reflective of each other and how we measure mental ill-health largely affect the conclusions we draw. The mental ill-health indicators which suggest there is an increase in mental ill-health (in- and outpatient diagnosis) partly depend on attitudes, help-seeking behaviour and diagnostic practice. Thus, we cannot say that mental ill-health actually has increased. However, all mental ill-health indicators are becoming increasingly concentrated among women and among those not participating in the labour force, and psychiatric diagnoses are increasingly concentrated among those lowest educated. Income-related mental health inequalities in Sweden are substantial, and have increased significantly between 1994 and 2011, both regarding absolute and relative inequalities. More than 30 percent of self-reported anxiety and suicides, and half or all psychiatric in- and outpatient diagnoses, are found among the poorest fifth of the population. The decomposition results show that distributional changes in the population explain the increase in suicide inequality and partly explain the increase in psychiatric inpatient diagnosis inequality. However, overall, only small changes in the level of mental ill-health and mental health inequalities are explained by changes in the population characteristics we study.
Keywords: I10; I14; 330; Mental health; Inequality in health; Concentration index; Decomposition